Evaluasi Keakuratan Informasi dan Kemudahan Pengguna Sistem Pakar berdasarkan Kepuasan Pengguna - Wicaksono, Andri Permana; Mudiono, Demiawan Rachmatta Putro; Muflihatin, Indah (Politeknik Negeri Jember, 2024)
This study, the application of an expert system for hepatitis disease which was made last year has been developed so that it is now being developed based on user satisfaction. The purpose of this study is to evaluate the value of user convenience and the accuracy of the existing information system in the hepatitis expert system application. This type of research is descriptive quantitative with a cross sectional approach. While this research is described in multiple linear regression analysis and descriptive analysis. The results of user convenience with an average of 3.4 and descriptive of the accuracy of information get an average value of 3.0. The results of the ease of use show that there is a significant effect on user satisfaction and the multiple linear regression analysis shows the accuracy of the information and does not have a significant effect on user satisfaction.